Irrigation as an alternative to reduce damages caused by defoliation of sweet corn - Santos, Osvaldir F. [UNESP]; Lima, Sebastião F.; Piati, Gabriel Luiz; Barzotto, Gustavo R.; Gava, Ricardo (FapUNIFESP (SciELO), 2018)
Reduction of leaf area significantly affects maize productivity, due to its low plasticity. Thus, appropriate water application can minimize this problem, considering that under favorable water conditions the plant would express its maximum production potential. The aim of this study was to evaluate the influence of irrigation on the productive performance of sweet corn submitted to different defoliation levels at the beginning of crop cycle. The experimental design was a randomized block design, arranged in split plot scheme; plots consisting of four water depths [50, 75, 100 and 125% of crop evapotranspiration (ETc)] and the subplots consisted of three defoliation levels [0% (control); 35% (removal of four fully expanded leaves), 100% (total removal of leaves, shoot section)], with three replicates. The use of irrigation has a positive influence on recovery of damages caused by defoliation at the initial development stages of sweet corn, and the success of irrigation management, as a strategy to mitigate damages caused by defoliation, depends on the level of the lost leaf area and the amount of water used.
Irrigação como alternativa para reduzir os prejuízos ocasionados por desfolha do milho doce
Keywords: Grain yield; Leaf area; Water availability; Zea mays